Property aspects of intellectual property / Ole-Andreas Rognstad, University of Oslo. - Rognstad, Ole-Andreas (Cambridge intellectual property and information law., 2018)
For many years, there have been discussions about whether intellectual property (IP) is really property. The property concept, particularly when used in transnational and international concepts, remains somewhat elusive. Here, Ole-Andreas Rognstad comprehensively discusses the use of the property metaphor in relation to IP in a transnational perspective. Rognstad gives an overview of main aspects of the IP/property interface, notably the justification and the structuring of the rights and intellectual property rights as assets. Moreover, he highlights the importance of distinguishing between these aspects, even though they are closely linked to each other. The book takes a transnational approach, dealing with recent developments in European human/fundamental rights law and international investment law, helping readers to understand the practical implications of the IP/property interface. This will be valuable reading for academics, practitioners and policy makers working in the area of IP, and lawyers and philosophers interested in the property debate.